Current trends in paediatric enteral tube feeding. Issue 8 (August 2021) - Bakewell, Christopher; Corlett, Chloe; Sharrard, Alison; Howarth, Lucy J.; Lee, Alex CH.
Abstract: The demand for enteral tube feeding in children is increasing globally. As our ability to manage complex medical conditions improves, so too does our understanding of the benefits of good enteral nutrition on health outcomes for these children. If oral feeding is not possible, an enteral tube can provide a viable alternative by delivering nutrition directly into the stomach or jejunum. The decision to recommend a child for long term tube feeding is complex and needs to be balanced against the potential risks. It is therefore essential that healthcare professionals keep up to date with the indications for referral, understand the current options available to children, and are able to identify common and serious problems that can arise following tube insertion. Healthcare professionals should also be aware of the debate surrounding the administration of blended feeds via the enteral tube. While some children may benefit from this practice, there are important considerations to be made for children receiving home blended feeds versus enteral formula. In this article, we review the indications for enteral tube insertion, device selection, complications and subsequent management. In addition, we review the logistics and implications for families and healthcare teams aiming to start blended tube feeding.